Controlling Islamic Education Marketing Services at MTs Negeri 4 Musi Banyuasin - Jumiati; Zainal Berlian; Ahmad Zainuri (The Future of Education Journal, 2025)
This study aims to analyze the control system of Islamic education marketing services in MTs Negeri 4 Musi Banyuasin. This study uses a descriptive qualitative research approach that consists of good words from the informants and the observed treatment. The data collection techniques in this study are using observation, interviews and documentation. The results of this study show that MTs Negeri 4 Musi Banyuasin already has a marketing team that plays a role in the implementation of strategies, such as SWOT analysis, service differentiation, and strengthening flagship programs. However, the optimization of digital platforms and program evaluation still need to be improved. The control system is carried out through regular monitoring, performance indicators (KPIs), and periodic evaluations. This strategy has succeeded in increasing the number of student enrollees from 96 in 2023 to 111 in 2024. This study concludes that effective control contributes to the success of marketing Islamic educational institutions. Recommendations were given for digitization of the marketing system, training of marketing teams, and promotion innovations to increase the competitiveness of institutions in the digital era.